N-glycomic Complexity in Anatomical Simplicity: Caenorhabditis elegans as a Non-model Nematode? - Paschinger, Katharina; Yan, Shi; Wilson, Iain B. H. (Frontiers in Molecular Biosciences, 2019)
Caenorhabditis elegans is a genetically well-studied model nematode or ‘worm’; however, its N-glycomic complexity is actually baffling and still not completely unravelled. Some features of its N-glycans are, to date, unique and include bisecting galactose and up to five fucose residues associated with the asparagine-linked Man2-3GlcNAc2 core; the substitutions include galactosylation of fucose, fucosylation of galactose and methylation of mannose or fucose residues as well as phosphorylcholine on antennal (non-reducing) N-acetylglucosamine. Only some of these modifications are shared with various other nematodes, while others have yet to be detected in any other species. Thus, C. elegans can be used as a model for some aspects of N-glycan function, but its glycome is far from identical to those of other organisms and is actually far from simple. Possibly the challenges of its native environment, which differ from those of parasitic or necromenic species, led to an anatomically simple worm possessing a complex glycome.